Discontinuation of adalimumab after achieving remission in patients with established rheumatoid arthritis: 1-year outcome of the HONOR study. Issue 2 (28th November 2013) - Tanaka, Yoshiya; Hirata, Shintaro; Kubo, Satoshi; Fukuyo, Shunsuke; Hanami, Kentaro; Sawamukai, Norifumi; Nakano, Kazuhisa; Nakayamada, Shingo; Yamaoka, Kunihiro; Sawamura, Fusae; Saito, Kazuyoshi
Abstract : Objectives: To investigate the possibility of discontinuing adalimumab (ADA) for 1 year without flaring (DAS28-erythrocyte sedimentation rate (ESR) ≥3.2), and to identify factors enabling established patients with rheumatoid arthritis (RA) to remain ADA-free. Methods: Of 197 RA patients treated with ADA+methotrexate (MTX), 75 patients who met the ADA-free criteria (steroid-free and sustained DAS28-ESR remission for 6 months with stable MTX doses) were studied for 1 year. Results: The mean disease duration and DAS28-ESR score in 75 patients was 7.5 years and 5.1 at baseline, respectively. The proportion of patients who sustained DAS28-ESR <2.6 (48%) and DAS28-ESR <3.2 (62%) for 1 year were significantly lower in the ADA discontinuation group than in the ADA continuation group; however, in patients with deep remission (DAS28-ESR ≤1.98) identified by receiver operating characteristics analysis following logistic analysis, these rates increased to 68% and 79%, respectively, with no significant difference between both groups. Remarkably, ADA readministration to patients with flare was effective in returning DAS28-ESR to <3.2 within 6 months in 90% and 9 months in 100% patients; among the patients who sustained DAS28-ESR <3.2 during ADA discontinuation, 100% remained in structural remission and 94% in functional remission. Conclusions: The possibility of remaining ADA-free for 1 year was demonstrated in established patients with RA with outcomes that ADA can be discontinued without flaring in 79% patients with deep remission, with similar rates in the ADA continuation group, and showed no functional or structural damage in patients with DAS28-ESR <3.2. ADA readministration to patients with flare during ADA discontinuation was effective.